Persepsi Penonton pada Film “27 Steps of May” - Melly Dwina; Nyoman Puspadarmaja (UNISBA Press, 2023)
Abstract. Film is a series of moving images and produces a story called a movie. The relationship between communication and film is that with communication, the process of making a film will be easier because it can avoid miss communications between individuals in the process of making a film. The film